Ubiquitin-Binding Protein CG5445 Suppresses Aggregation and Cytotoxicity of Amyotrophic Lateral Sclerosis-Linked TDP-43 in Drosophila. - Uechi, H.; Kuranaga, E.; Iriki, T.; Takano, K.; Hirayama, S.; Miura, M.; Hamazaki, J.; Murata, S. (Molecular and Cellular Biology, 2018)
Ubiquitin-mediated protein degradation plays essential roles in proteostasis and is involved in the pathogenesis of neurodegenerative diseases in which ubiquitin-positive aberrant proteins accumulate. However, how such aberrant proteins are processed inside cells has not been fully explored. Here, we show that the product of CG5445, a previously uncharacterized Drosophila gene, prevents the accumulation of aggregate-prone ubiquitinated proteins. We found that ubiquitin conjugates were associated with CG5445, the knockdown of which caused the accumulation of detergent-insoluble ubiquitinated proteins. Furthermore, CG5445 rescued eye degeneration caused by the amyotrophic lateral sclerosis (ALS)-linked mutant TAR DNA-binding protein of 43 kDa (TDP-43), which often forms ubiquitin-positive aggregates in cells through the capacity of CG5445 to bind to ubiquitin chains. Biochemically, CG5445 inhibited the accumulation of insoluble forms and promoted their clearance. Our results demonstrate a new possible mechanism by which cells maintain ubiquitinated aggregation-prone proteins in a soluble form to decrease their cytotoxicity until they are degraded.